Man Alive : the magazine of Britain's top physique photographers. (London : Man Alive Publications Ltd., 1958)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Man Alive Photo House, 10 St. Martin's Court, London WC 2 ; vanaf (1961) 3 : Suite 34, 3 Golden Square, London W 1
Engels
Periodiek